The Contribution of the Airway Epithelial Cell to Host Defense - Frauke Stanke (Mediators of Inflammation)
In the context of cystic fibrosis, the epithelial cell has been characterized in terms of its ion transport capabilities. The ability of an epithelial cell to initiate CFTR-mediated chloride and bicarbonate transport has been recognized early as a means to regulate the thickness of the epithelial lining fluid and recently as a means to regulate the pH, thereby determining critically whether or not host defense proteins such as mucins are able to fold appropriately. This review describes how the epithelial cell senses the presence of pathogens and inflammatory conditions, which, in turn, facilitates the activation of CFTR and thus directly promotes pathogens clearance and innate immune defense on the surface of the epithelial cell. This paper summarizes functional data that describes the effect of cytokines, chemokines, infectious agents, and inflammatory conditions on the ion transport properties of the epithelial cell and relates these key properties to the molecular pathology of cystic fibrosis. Recent findings on the role of cystic fibrosis modifier genes that underscore the role of the epithelial ion transport in host defense and inflammation are discussed.